LncR26319/miR‐2834/EndophilinA axis regulates oogenesis of the silkworm, Bombyx mori. (15th June 2022) - Wang, Yi; Fu, Yu; Cheng, Hao; Zhao, Chenyue; Huang, Qunxia; Chang, Meiling; Qiu, Wujie; Shen, Yawen; Li, Dandan
Abstract: Oocyte maturation is critical for insect reproduction. Vitellogenesis, the timely production and uptake of vitellogenin (Vg), is crucial for female fecundity. Vg is synthesized in fat body and absorbed by the oocytes through endocytosis during insect oogenesis. In the silkworm, Bombyx mori, we discovered that a nucleus‐enriched long‐noncoding RNA (lncRNA) lncR26319 regulates Endophilin A ( EndoA ) – a member of the endophilin family of endocytic proteins – through competitive binding to miR‐2834. The lncR26319‐miR‐2834‐ EndoA axis was required for Vg endocytosis in the silkworm; loss of EndoA or overexpression of miR‐2834 significantly reduced egg numbers in virgin moths. In addition, accumulation of miR‐2834 resulted in pupal and adult deformation and reduced fecundity in females. The expression of Vg, 30‐kDa (30K) protein, and egg‐specific protein (Esp) decreased after knockdown of EndoA or overexpression of miR‐2834, while knockdown of miR‐2834 had an opposite effect on the expression of Vg, 30K protein gene, and Esp . These results suggest that the lncR26319‐miR‐2834‐ EndoA axis contributes to the endocytic activity in the Vg uptake and leads to the normal progression of oogenesis in the silkworm. Thus, miR‐2834 and EndoA are crucial for female reproduction and could be potential targets for new pest management strategies in lepidopterans. Abstract : Vitellogenesis, the timely production and uptake of yolk proteins, is essential for female fecundity. In the silkworm, Bombyx mori, a nucleus‐enriched long‐noncoding RNA (lncRNA) lncR26319 regulates Endophilin A ( EndoA ), a member of the endophilin protein family of endocytosis, by competitively binding to miR‐2834. The lncR26319‐miR‐2834‐ EndoA axis contributes to the endocytic activity in the yolk uptake process and leads to the normal progression of oogenesis in the silkworm.